Assessing the feasibility of an integrated CLC-methanation system using solar dried and torrefied biomasses as a feedstock. (1st January 2023) - Brachi, P.; Bareschino, P.; Tregambi, C.; Pepe, F.; Urciuolo, M.; Ruoppolo, G.; Mancusi, E.
Highlights: A novel layout for biomass waste torrefaction, CLC, and methanation is proposed. LHV of agro-industrial residues torrefied at 300 °C increased by about 14–49 %. A CO2 -to-CH4 conversion degree higher than 98% was evaluated. Solar-driven torrefaction enhances the renewable footprint of the proposed process. Abstract: To promote the integration between solar-driven torrefaction, Power-to-Gas, and Chemical Looping Combustion (CLC) systems, this work numerically analyzes the performances of a novel process layout. Several agro-industrial residues were considered as fuels. CuO supported on zirconia and Ni supported on alumina were considered as oxygen carrier and methanation catalyst, respectively. Torrefied samples were purposely obtained by means of experimental runs carried out for 30 min at 300 °C in a lab-scale fixed bed reactor under a nitrogen atmosphere. Under the adopted conditions it was attained an increase in the lower heating values (LHV) of the selected feedstocks by about 14–49 %, depending on the different composition and reactivity of the parent biomass. Based on these data, it was estimated that, with respect to 10 kg h −1 torrefied biomass fed to the CLC system, a total thermal power production in the range of 28–58 kW can be achieved. CO2 conversion degrees of above 98 % were evaluated for the methanation unit in all considered scenarios. Considering different locations in Italy, PV field sizes ranging from 45 m 2 up to 1392 m 2 were evaluated for the solar-driven torrefaction unit. Wider sizes were calculated for the hydrogen production one, ranging from 3366 m 2 up to 5598 m 2 . Eventually, an electric energy storage efficiency of around 16 % was assessed for the proposed layout. Finally, it was found that moving from the adopted torrefied feedstocks to the produced gaseous fuel, an increase in the LHV by about 44–55 % can be attained, while concurrently, CO2 emissions are favorably decreased by 98 %.